Pengaruh Modal Sosial, Literasi Digital dan Orientasi Kewirausahaan terhadap Keberlanjutan Usaha Mikro Kecil di Kelurahaan Sitirejo Kecamatan Medan Amplas - Feni Damayanti; Julianto Hutasuhut; Toni Hidayat; Yayuk Yuliana; Wan Dian Safina (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of social capital, digital literacy, and entrepreneurial orientation on the sustainability of micro and small enterprises (MSEs) in Sitirejo Village, Medan Amplas District. MSEs are important pillars in the local economy, but still face various challenges such as limited access to capital, low utilization of digital technology, and lack of innovation and market adaptation. The approach used in this study is a quantitative approach with multiple linear regression analysis techniques. The population in this study were all MSE actors in Sitirejo Village totaling 85 respondents, where the sampling technique used the saturated sampling technique. Data were collected through questionnaires and analyzed using SPSS software versions 30 and 25. The results of the study are expected to show that social capital, digital literacy, and entrepreneurial orientation, both partially and simultaneously, have a significant influence on business sustainability. This study provides an important contribution to MSE actors, academics, and the government in designing sustainable business development strategies through strengthening social networks, increasing digital literacy, and strengthening entrepreneurial orientation.